1014 Relationship Between Lung Function and Obstructive Sleep Apnea in Cystic Fibrosis. (27th May 2020) - Shakkottai, A; Nasr, S Z; Hassan, F; O'Brien, L M; Chervin, R D
Abstract: Introduction: The frequency of obstructive sleep apnea (OSA) may be high among patients with cystic fibrosis (CF), a life-shortening, genetic respiratory disease that affects approximately 30, 000 Americans. Yet, the potential relationship between OSA and lung function has not been thoroughly explored. Methods: Single-center retrospective review of polysomnography (PSG) results from 2009-2017 in referred patients with CF and available pulmonary function data (PFTs) obtained at time of PSG and at 3, 6, 9, and 12-months prior. Results: Mean ages were 11.1±3.9 (sd) and 37.1±14.1 years, among 18 children and 16 adults, respectively. Mean body mass index (BMI) was normal in both groups (62.5±26.6% in children; 25.1±6.4 kg/m 2 in adults). Twenty-six subjects (76%) had OSA (apnea-hypopnea index >1 in children, ≥5 in adults). Mean forced expiratory volume in 1 second percent predicted (FEV1 PPD) was higher among subjects with vs. without OSA at PSG and at each time-point in the year prior, independent of age and BMI at PSG (longitudinal mixed effects model, β=19.0, SE=8.1, p=0.028). While FEV1 PPD remained unchanged in the non-OSA group, FEV1 PPD at PSG was lower, in comparison to the year prior in subjects with OSA, with the greatest difference observed at 9-months prior to PSG (2-sample t-test, difference of -6.6% vs 0.6% in OSA vs. non-OSA groups respectively, p=0.078). Conclusion: The PFTs, as daytime markers of CF lung disease severity, do not seem to reliably predict risk for OSA. In our sample, CF patients with vs. without OSA had better PFTs at baseline but they also showed a greater tendency for decline in PFTs over the year prior to OSA diagnosis. Larger sample size and longer duration of assessment may help, going forward, to assess any potential adverse impact of OSA on lung function decline. Support: NIH Training Grant (T32NS007222, F32HL145915)